New Insights Into Multicenter PICU Mortality Among Pediatric Hematopoietic Stem Cell Transplant Patients*. Issue 9 (September 2015) - Zinter, Matt S.; Dvorak, Christopher C.; Spicer, Aaron; Cowan, Morton J.; Sapru, Anil
Abstract : Objectives: Over 2, 500 children undergo hematopoietic stem cell transplantation in the United States each year, and up to 35% require PICU support for life-threatening complications. PICU mortality has dropped from 85% to 44%, but interpretation is confounded by significant cohort heterogeneity. Reports conflict regarding outcomes for patients with different underlying hematopoietic stem cell transplantation indications, and the burden of infectious complications for these patients has not been evaluated. We aim to describe infections, critical care interventions, and mortality for pediatric hematopoietic stem cell transplantation patients requiring PICU admission. Design: A retrospective multicenter cohort analysis. Setting: One hundred twelve centers in the Virtual PICU Systems database, January 1, 2009, to June 30, 2012. Patients: A total of 1, 782 admissions for patients who are 21 years old or younger with prior hematopoietic stem cell transplantation. Interventions: None. Measurements and Main Results: Pediatric Index of Mortality-2, Pediatric Risk of Mortality-3, transplant indication, infections, interventions, and mortality were recorded from admission through PICU death or discharge. Pediatric hematopoietic stem cell transplantation patients comprised 0.7% of all PICU admissions (1, 782/246, 346), which resulted in 16.2% mortality compared with 2.4% mortality for non–hematopoietic stem cell transplantation admissions (odds ratio, 7.8; 95% CI, 6.8–8.8; p < 0.001). Mortality for admissions with underlying hematologic malignancy (22.7%) was similar to that of admissions with primary immunodeficiency (19.4%; p = 0.41) but significantly greater than admissions with underlying nonmalignant non–primary immunodeficiency hematologic disease (15.4%; p = 0.020), metabolic disorder (8.1%; p < 0.001), or solid malignancy (5.7%; p < 0.001). Infection was documented in 45.7% of admissions with 22.2% mortality; viral and fungal mortality were 28.5% and 33.7%, respectively. Invasive positive pressure ventilation and renal replacement therapy were used in only 34.6% and 11.9% of admissions, with mortality of 42.5% and 51.9%, respectively. Conclusions: PICU mortality for pediatric hematopoietic stem cell transplantation patients may be as low as 16.2% but higher for those receiving intubation (42.5%) or replacement therapy (51.9%). Hematologic malignancy and primary immunodeficiency had greater risk for mortality than other transplant indications. Greater understanding of other risk factors affecting mortality and the need for critical care support is needed. Abstract : Supplemental Digital Content is available in the text.